The Utilization of Flashcards in Teaching English Vocabulary to Young Learners - Agnesia, Wega Dhea; Nurwadi, Nurul Fadilah; Suharyadi, Suharyadi; Anugerahwati, Mirjam; Khoiri, Niamika El (Universitas Cokroaminoto Palopo, 2025)
This study aims to investigates the effectiveness of using flashcards to teach English vocabulary to young learners. The research was conducted at SDN Gempol 2 with 36 third-grade students. A one-group pre-experimental design was employed, using pre-test and post-test to collect the data. The results revealed a significant improvement in students' vocabulary mastery, with the average score increasing from 65.83 (pre-test) to 76.80 (post-test). Statistical analysis showed that the t-value (11.056) exceeded the critical value (2.035), and the significance level (p = .000) was below the threshold of 0.05, indicating a meaningful difference. These findings suggest that flashcards are an effective tool for enhancing vocabulary acquisition among young learners, as they help maintain students’ engagement through visual and interactive learning.